How socio-cultural factors affect cervical cancer screening adherence and treatment in disadvantaged communities in the greater Cape Town, South Africa. - De Abreu, Chantelle Silva (Department of Psychology, 2015)
Approximately 85% of the global cervical cancer deaths occur in women living in developing countries. In South Africa, cervical cancer is the second most common cancer amongst women, with Black South African women having the highest risk of developing cervical cancer. Previous research with the same population group found that there are structural (time, health education, age) and psychosocial (fear of screening and stigmatization) influences to cervical screening. The purpose of this research was to identify socio-cultural factors affecting cervical cancer screening adherence within a disadvantaged community in South Africa, a developing country. To identify the social-cultural factors four focus groups consisting of men and women between the ages of 18 and 60 were conducted. A combination of the Health Belief Model (HBM) and Theory of Reasoned Action (TRA) provided a theoretical framework for this study. Thematic analysis was used to identify themes that emerged from the focus groups and participant observation. Through conducting these focus groups, themes emerged which strongly highlighted the role of cultural norms, gender roles, the western medical model and traditional medicine in a woman’s decision to adhere to cervical screening. It was found that factors such as knowledge and stigma, found previously in research, were also shared amongst this sample group. However, spiritual and religious beliefs (traditional healers, religion, and balancing paradigms), gender beliefs, social construction and acceptance of disease were factors which also emerged as exerting influence in a woman’s decision to adhere to cervical screening.